Penggunaan Multi Metode untuk Meningkatkan Kemampuan Membaca dan Menulis Permulaan Siswa Kelas 1 SD - Tresna Purnama Dewi; Milla Mustikawati Sugandi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was conducted to improve students' reading and writing skills. Because the ability to read and write the beginning is still very low. The use of multiple methods as a solution to be used in the learning process is a strategy to be able to achieve learning objectives. This research method is based on Classroom Action Research (PTK) which in the process carries out several stages including planning, implementation, observation and reflection. The subject of this study is a student of 1st grade SDN 2 Sodong. The data collection technique uses a qualitative descriptive approach and is presented in tabular form. The research was conducted in 2 cycles, cycle 1 showed the results that the completeness of beginning reading was 46% and the completeness of beginning writing was 38.4%. In Cycle 2 there was a very significant change with reading and writing completeness of 85%. Thus, the use of multi-methods is proven to improve reading and writing skills in grade 1.